Clinical Isolates of Acinetobacter spp. Are Highly Serum Resistant Despite Efficient Recognition by the Complement System - Magda, Michal; Bettoni, Serena; Laabei, Maisem; Fairley, Derek; Russo, Thomas A.; Riesbeck, Kristian; Blom, Anna M. (Frontiers in Immunology, 2022)
Gram-negative bacteria from the genus Acinetobacter are responsible for life-threating hospital-related infections such as pneumonia, septicemia, and meningitis, especially in immunocompromised patients. Worryingly, Acinetobacter have become multi- and extensively drug resistant (MDR/XDR) over the last few decades. The complement system is the first line of defense against microbes, thus it is highly important to increase our understanding of evasion mechanisms used by Acinetobacter spp. Here, we studied clinical isolates of Acinetobacter spp. (n=50), aiming to characterize their recognition by the complement system. Most isolates tested survived 1 h incubation in 30 % serum, and only 8 isolates had a lower survival rate, yet none of those isolates were fully killed. Intriguingly, four isolates survived in human whole blood containing all cell component. Their survival was, however, significantly reduced. Flow cytometry analyses revealed that most of the isolates were detected by human IgG and IgM. Interestingly, we could not detect any significant concentration of deposited C1q, despite observing C4b deposition that was abolished in C1q-deficient serum, indicating transient binding of C1q to bacteria. Moreover, several isolates were recognized by MBL, with C4b deposition abolished in MBL-deficient serum. C3b was deposited on most isolates, but this was not, however, seen with respect to C5b and formation of the membrane attack complex (MAC), indicating that many isolates could avoid complement-mediated lysis. India ink staining showed that isolates were capsulated, and capsule thickness varied significantly between isolates. Studies performed on a wild-type strain and capsule mutant strains, demonstrated that the production of a capsular polysaccharide is one mechanism that mediates resistance to complement-mediated bactericidal activity by preventing MAC deposition and lysis. Our data showed that most clinical Acinetobacter spp. isolates are highly serum resistant despite being efficiently recognized by the complement system.